Transforming Africa’s agriculture through enhancing commercialization of agricultural research products: The case of high iron beans technology - Mabeya, Justin; Kamanda, Josey; Onyango, Patricia; Eshetu, Samson; Bheenick, Krishan; Munoko, Karen; Abugri, Benjamin (2021)
High Iron Beans is one of the commodity value chains supported under TAAT. The HIB Value Chain compact aims at increasing the HIB productivity from 0.8 to 1.2 MT/ha for bush beans and 1.5 to 2.5 MT/ha for climbing beans, produce additional 800,000 MT of HIB in target countries, create access to seed, growing and consuming HIB for 2 million households. Besides increasing productivity and creating access to seeds, the project using the “Commodity Corridor Approach” works at enhancing business opportunities and investments for the youth through inputs distribution and access to markets and value addition for grain. Burundi, DR Congo, Kenya, Malawi, Rwanda, Tanzania, Uganda and Zimbabwe are the target countries for large scale deployment of the HIB technologies.